Children Learn About God Swt (Studying God with Primary Children 6-12 Years) - Muhammad Shaleh Assingkily; Khamim Zarkasih Putro (AIUA Journal of Islamic Education, 2020)
Religion and God, not taboo to be taught to children of basic age (6-12 years). This article aims to examine pedagogics that deserve to be taught to children about their God (Allah swt.) And know the limits of basic age children to know God according to their developmental stages. The formulation of the problem in this study is what are the boundaries that are taught to children (basic age) about God and how to study God with students of basic age. This study uses a qualitative approach with library study methods. The results of this study indicate that (1) know God Almighty. to children limited in the cognitive dimension according to the stage of development of the child's religion, while the feeling of God and the awareness of God for children can be taken through concrete worship practices. (2) The efforts that should be done by adults in studying God with basic age children based on the stage of development are (a) instilling monotheism through the majesty of God, (b) introducing Allah Almighty. through the child, (c) educating the child with worship, and (d) displaying the moral virtues as a reflection of Asma al-Husna.